2018
DOI: 10.1039/c8gc02295j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of perfectly ordered mesoporous carbons by water-assisted mechanochemical self-assembly of tannin

Abstract: Water-assisted mechanosynthesis allows preparing perfectly ordered mesoporous carbons from tannins without crosslinkers or any drying or curing step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 66 publications
1
53
0
Order By: Relevance
“…To address this key issue, extensive studies have been done to develop high-performance electrode materials, including conducting polymers [12,13], heteroatomdoped carbon materials [14][15][16][17][18][19], transition metal phosphates [20], and transition metal oxides/hydroxides [21][22][23][24][25][26][27]. Lin et al [28] reported a nitrogen-doped mesoporous carbon, of which the specific capacitance can reach to 855 F g −1 at 1 A g −1 in 0.…”
Section: Introductionmentioning
confidence: 99%
“…To address this key issue, extensive studies have been done to develop high-performance electrode materials, including conducting polymers [12,13], heteroatomdoped carbon materials [14][15][16][17][18][19], transition metal phosphates [20], and transition metal oxides/hydroxides [21][22][23][24][25][26][27]. Lin et al [28] reported a nitrogen-doped mesoporous carbon, of which the specific capacitance can reach to 855 F g −1 at 1 A g −1 in 0.…”
Section: Introductionmentioning
confidence: 99%
“…9 Many efforts to synthesise OMCs from biosourced materials by hard-and soft-templating methods have been made. [10][11][12][13][14][15][16][17] In particular, condensed tannins extracted from trees (mimosa, quebracho and pine, among others), which are principally based on flavonoid-type polyphenols, are able to undergo autocondensation reactions and hence do not require using crosslinkers. 18 This remarkable feature makes them suitable, non-toxic and environment-friendly alternative carbon precursors to resorcinol or phenol.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical energy generated from grinding or shearing can increase the contact area and enhance the interaction between the precursors . In the reported studies, ordered mesoporous carbons can be produced from the ball milling of carbon precursors and templates . Ball milling is considered as a suitable method as it can not only afford higher mechanical energy with repeatability than those by hand‐grinding but also avoid the waste of solvents and thus meets the requirements of green industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanochemical solid‐state synthesis is an efficient method to synthesize various inorganic materials and organic materials, for it comprises fewer synthesis steps and can be implemented with low amounts of solvents or even under solvent‐free conditions . Mechanical energy generated from grinding or shearing can increase the contact area and enhance the interaction between the precursors . In the reported studies, ordered mesoporous carbons can be produced from the ball milling of carbon precursors and templates .…”
Section: Introductionmentioning
confidence: 99%